Perancangan Ruang Yoga Dan Pottery ART Di Rumah Sakit Jiwa Soeharto Heerdjan Berkonsep Wabi-Sabi - Salsabila, Salsabila; Wiyono, Erina; Kertapati, Wisnoe Akbar (Innovative: Journal Of Social Science Research, 2025)
Mental health challenges in Indonesia necessitate enhanced psychosocial rehabilitation services in psychiatric hospitals. This study designs yoga and pottery art spaces at Soeharto Heerdjan Psychiatric Hospital using wabi-sabi design principles to support therapeutic recovery. A qualitative case study methodology was employed, following Rosemary Kilmer's interior design framework. Data collection included field observations, semi-structured interviews, and documentation analysis, with thematic analysis applied to findings. The design demonstrates that wabi-sabi principles is natural materials, neutral colors, and acceptance of imperfection create therapeutic environments promoting healing, emotional comfort, and patient self-acceptance. The yoga room incorporates therapeutic elements including natural lighting and organic textures, while the pottery art room facilitates creative expression through ergonomic furniture and meaningful art installations. This design serves as a model for humanistic therapeutic interior design in mental health facilities.